PERAN STRUKTUR KEPEMILIKAN DALAM MEMPENGARUHI KONSERVATISME AKUNTANSI - Rais, Fiqriah A.; Praditha, Riza (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the role of a company's capital ownership structure in influencing accounting conservatism practices. The ownership structures used in this study are managerial ownership, institutional ownership, and foreign ownership. The subjects of this study were companies indexed in the LQ45 on the Indonesia Stock Exchange. Subjects were selected as samples using a purposive sampling method, and a total of 72 participants were selected. Data were analyzed using multiple linear regression analysis. The results show that managerial ownership plays a role in increasing the potential for conservative practices. The greater the managerial ownership of a company, the greater the practice of accounting conservatism. Different results were obtained from testing institutional ownership and foreign ownership, which did not have a significant impact on accounting conservatism.